Assessing Communicative Language Ability By Means Of Bachman And Palmer's Model - Naoua, Mohammed (University of Eloued جامعة الوادي, 2017)
Assessing communicative language ability refers to the process of collecting data by means of tests in order to make inferences about test takers' levels of language knowledge, and to measure the extent to which they can use this knowledge in contextual target situations. According to Bachman and Palmer (1996), this process requires the outline of frameworks delimiting the constructs to be tested and the development of methods describing how these constructs can be measured. The main aim of this article is to introduce Bachman and Palmer's (1996) conceptualization of language assessment, which can be used as a basis for developing valid and reliable tests. تهدف اختبارات اللغة الانجليزية حسب نموذج بكمان وبـــالمر (Bachman & Palmer, 1996) إلى قياس مستوى الكفاءة اللغوية للممتحنين وكذا مدى تمكنهم من استعمال هذه الكفاءة في سياقات مماثلة لمجالات دراستهم. ولكي تعكس النتائج المحتصل عليها في هذه الاختبارات المستوى الفعلي للممتحنين يقترح العالمان نموذجا يصف ماهية وكيفية عملية القياس والتقييم في المجال اللغوي. تحدد المرحلة الأولى من هذا النموذج الكفاءات الفرعية المستهدفة بالقياس وتبيّن مرحلته الثانية طرق وكفيات قياس تلك الكفاءات. تبين هذه الورقة أن استعمال نموذج بكمان وبـــالمر (Bachman & Palmer, 1996)لقياس الكفاءة التواصلية يؤدي إلى بناء اختبارات ذات مستوى عال من الصحة والصدقية
قياس الكفاءة التواصلية بواسطة نموذج بكمان وبالمر
مجلة البحوث والدراسات المجلد 14 العدد 02 جامعة الوادي
Keywords: Assessment – measurement – communicative competence -Tests; التقييم – القياس – الكفاءة التواصلية – الاختبارات